2003
DOI: 10.18553/jmcp.2003.9.6.544
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Cost-Effectiveness of Statins

Abstract: In order to optimize cost-effectiveness, the level of effectiveness required to treat the specific patient or patient group must be considered. Statin efficacy is the major determinant of cost-effectiveness when greater cholesterol lowering is required, i.e., for high-risk patients, who make up the primary target group. Statin price is the more important factor if only limited cholesterol lowering (e.g., 35% or less reduction in LDL) is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…19 However, our study found that almost two-thirds of participants who were at high risk for developing CHD within 10 years and who were eligible for lipid-lowering drugs were not receiving medication. Our estimates would be even higher had we used the modification of the LDL-C goal for high-risk patients of less than 70 mg/dL recommended by the updated 2004 NCEP ATP III report.…”
mentioning
confidence: 61%
“…19 However, our study found that almost two-thirds of participants who were at high risk for developing CHD within 10 years and who were eligible for lipid-lowering drugs were not receiving medication. Our estimates would be even higher had we used the modification of the LDL-C goal for high-risk patients of less than 70 mg/dL recommended by the updated 2004 NCEP ATP III report.…”
mentioning
confidence: 61%
“…22 Because the majority of hyperlipidemia patients do not have existing cardiovascular disease, we base our analysis of the costeffectiveness of DTCA on the efficacy of statins for primary prevention. The efficacy of statins for secondary prevention has been shown to be larger than that for primary prevention (Morrison & Glassberg, 2003). Our estimate of effectiveness of DTCA is therefore conservative.…”
Section: Public Policy Implicationsmentioning
confidence: 91%
“…20 The market introduction of rosuvastatin in late 2003 increased the attention to ever more powerful statins and the relative cost-effectiveness among these drugs. 21 Yet, managed care pharmacists should not lose sight of the cost per outcome in disease management of coronary heart disease (CHD). For example, comparison of 5 alternative prevention strategies in a patient at 10% coronary risk over 5 years showed that aspirin 75 mg per day is the most cost effective at £3,500 (British) pounds per CHD event prevented; 72% lower cost compared with initial treatment for hypertension with a diuretic (bendrofluazide 2.5 mg per day) and beta-blocker (50 mg atenolol per day; 12,500 pounds); 81% lower cost compared with the £18,300 for the initial thiazide + beta-blocker combination + enalapril (angiotensin-converting enzyme inhibitor) 20 mg per day; 94% lower cost than the £60,000 for clopidogrel 75 mg per day or the £61,400 for simvastatin 40 mg per day.…”
Section: Methods To Attain Optimal Outcomes With Lipid-lowering Drmentioning
confidence: 99%